Precision-engineered PROTACs minimize off-tissue effects in cancer therapy - Shi, Jianghua; Wang, Luo; Zeng, Xuanwei; Xie, Chengzhi; Meng, Zhaowei; Campbell, Anahit; Wang, Lulu; Fan, Heli; Sun, Huabing (Frontiers in Molecular Biosciences, 2024)
Proteolysis-targeting chimeras (PROTACs) offer a groundbreaking approach to selectively degrade disease-related proteins by utilizing the ubiquitin-proteasome system. While this strategy shows great potential in preclinical and clinical settings, off-tissue effects remain a major challenge, leading to toxicity in healthy tissues. This review explores recent advancements aimed at improving PROTAC specificity, including tumor-specific ligand-directed PROTACs, pro-PROTACs activated in tumor environments, and E3 ligase overexpression strategies. Innovations such as PEGylation and nanotechnology also play a role in optimizing PROTAC efficacy. These developments hold promise for safer, more effective cancer therapies, though challenges remain for clinical translation.